ʾA nā gātʻ phakʻ da rayʻ praññʻ thoṅʻ cu Mranʻ mā nuiṅʻ ṅaṃ : pvaiʹ caññʻʺ ʾupʻ khyupʻ puṃ ʾa khre khaṃ upade mū kramʻʺ phvaṅʻʹ chui khyakʻ - National Council of the Union of Burma ([Place of publication not identified] : National Council of the Union of Burma, 1997)
A federal constitution drafted by National Council of the Union of Burma during constitutional seminar in 1996 in exile.
Text in Burmese.
Includes bibliographical references (pages 234-236).
Keywords: Constitutional conventions -- Burma; Constitutional amendments -- Burma; Democracy -- Burma; Burma -- Politics and government -- 1988- .